2016
DOI: 10.1515/intag-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional specific physical properties of fan palm fruits, seeds and seed coats (Washingtonia robusta)

Abstract: A b s t r a c t. In this study some physical properties of fan palm (Washingtonia robusta) fruits, seeds and seed coats were determined using dimensional, bulk and single kernel physical analysis. The moisture content of whole fruits, seeds and seed coats was 12.0, 9.86 and 13.87% (d.b.), respectively. The sphericity values showed that seed shape (0.86) is close to a sphere, similar as the fruit shape (0.83), both of which were close to a scalene ellipsoid shape. The surface area values of fruits and seeds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The finding indicated that seeds will float in water while kernels will sink [39]. Furthermore, according to this information, the separation of the hulls can be carried out by blowing air instead of floating in water [64]. The decrease in overall true density with classes may be due to the decrease in water absorption caused by the oil molecules and the increase in proteins [65].…”
Section: Size Shape and Gravimetric Properties Of Sunflower Seeds And Kernelsmentioning
confidence: 94%
“…The finding indicated that seeds will float in water while kernels will sink [39]. Furthermore, according to this information, the separation of the hulls can be carried out by blowing air instead of floating in water [64]. The decrease in overall true density with classes may be due to the decrease in water absorption caused by the oil molecules and the increase in proteins [65].…”
Section: Size Shape and Gravimetric Properties Of Sunflower Seeds And Kernelsmentioning
confidence: 94%
“…Biomass partitioning is pulp 53.7 % and seed 46.3 % (Coşkuner & Gökbudak 2016). Comparing with sugars in others edible fruits occurring in the study area like, Vitex mollis (92 %) (Montiel-Herrera et al 2004), Washingtonia filifera (77 %) and the introduced Phoenix dactylifera (94 %) (Cornett 1987, Besbes et al 2004) therefore W. robusta (71 %) represents a comparative sugar resource.…”
Section: Discussionmentioning
confidence: 91%
“…Wendl., found in Baja California and Sonora (Nehdi 2011). Both species are cultivated as ornamentals around the world, particularly in California and in northwest Mexico, as well as in the Mediterranean basin, southern Europe, and some parts of Australia (Coşkuner & Gökbudak 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation